2021
DOI: 10.3389/fpsyg.2021.607639
|View full text |Cite
|
Sign up to set email alerts
|

Political Identity Over Personal Impact: Early U.S. Reactions to the COVID-19 Pandemic

Abstract: Research suggests political identity has strong influence over individuals’ attitudes and beliefs, which in turn can affect their behavior. Likewise, firsthand experience with an issue can also affect attitudes and beliefs. A large (N = 6,383) survey (Pew Research and Ipsos W64) of Americans was analyzed to investigate the effects of both political identity (i.e., Democrat or Republican) and personal impact (i.e., whether they suffered job or income loss) on individuals’ reactions to the COVID-19 pandemic. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 94 publications
(126 reference statements)
3
31
0
Order By: Relevance
“…Those who identified as Republicans were significantly less likely to hold positive COVID-19 vaccination beliefs such as believing in the value of vaccination to protect close others (e.g., family, friends, those who are vulnerable due to age, pre-existing conditions, etc.). This finding is in line with previous research that has identified party identification as a strong driver of COVID-19 prevention behavior ( Adolph et al, 2021 ; Bruine de Bruin, Saw and Goldman, 2020 ; Collins et al, 2021 ), but adds that party identification also influences the determinants of behavior, such as attitude structures as well as underlying beliefs. Given the importance of positive COVID-19 vaccination beliefs in determining attitudes, these findings are also consistent with previous research that has called for pro-vaccine messaging to promote vaccination, rather than messaging attempting to dispel vaccine myths ( Nyhan et al, 2014 ) (see Table 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Those who identified as Republicans were significantly less likely to hold positive COVID-19 vaccination beliefs such as believing in the value of vaccination to protect close others (e.g., family, friends, those who are vulnerable due to age, pre-existing conditions, etc.). This finding is in line with previous research that has identified party identification as a strong driver of COVID-19 prevention behavior ( Adolph et al, 2021 ; Bruine de Bruin, Saw and Goldman, 2020 ; Collins et al, 2021 ), but adds that party identification also influences the determinants of behavior, such as attitude structures as well as underlying beliefs. Given the importance of positive COVID-19 vaccination beliefs in determining attitudes, these findings are also consistent with previous research that has called for pro-vaccine messaging to promote vaccination, rather than messaging attempting to dispel vaccine myths ( Nyhan et al, 2014 ) (see Table 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our investigations into individual difference yielded mixed results. Prior research implicated political preference as a particularly strong predictor of COVID-19-related PERCEPTIONS OF SELF-OTHER DIFFERENCES 21 health behavior, even overriding perceptions of risk and other salient factors (Collins et al, 2021). Those results were corroborated by this study.…”
Section: Discussionsupporting
confidence: 83%
“…Political Preference. Political preference is particularly notable as a predictor in this study due to its demonstrated associations both with false consensus (Blanchar et al, 2021) and willingness to engage in health and safety measures (Urminsky & Bergman, 2021;Collins et al, 2021). Furthermore, older (Biernat et al, 1997) and more recent (Rabinowitz et al, 2016;Stern et al, 2014) studies have connected political identity (liberal vs. conservative) to both false consensus and false uniqueness, with liberals displaying more false uniqueness and conservatives displaying more false consensus.…”
Section: Individual Difference Measuresmentioning
confidence: 84%
“… 32 A nationwide study early in the pandemic also showed that political affiliation was related to threat perception and government response to the pandemic. 33 A study on Twitter found strong partisan reactions to the pandemic. 34 …”
Section: Discussionmentioning
confidence: 99%
“…32 A nationwide study early in the pandemic also showed that political affiliation was related to threat perception and government response to the pandemic. 33 A study on Twitter found strong partisan reactions to the pandemic. 34 In conclusion, several factors were related to resuming travel and leisure behaviors during the pandemic and prior to the availability of vaccines.…”
Section: Discussionmentioning
confidence: 99%